120 Use of the veterans crisis line among high-risk patients: does relationship status make a difference?. (19th September 2017) - Lindenauer, Samantha; Stewart, Haylie; Ciofu, Amanda; Jordan, Jennifer; Aldaco-Revilla, Laura; Kelly, Kendall; Shaw, Jessica
Abstract : Purpose: The Veterans Crisis Line (VCL) provides support in times of crisis and coordinates care with the goal of preventing injuries, hospitalizations, and deaths. However, very little is known about the extent to which Veterans at high risk for suicide utilise the VCL. An ongoing VA study, Link Up, examines the impact of a brief intervention aimed at increasing use of the VCL among Veterans recently hospitalised for suicidal crises. In order to better understand factors affecting the likelihood that Veterans will use the VCL, this poster examines the link between support from a romantic partner and use of this resource. Methods: 227 Veterans hospitalised for a recent suicidal crisis were asked about their relationship status (married or cohabitating vs. single, widowed, or divorced) and use of the VCL in the past year. An odds ratio was calculated to examine the association between relationship status and crisis line use. Results: Analysis showed no significant difference in the likelihood of VCL use between partnered and single Veterans, 18.3% and 23% respectively (Odds Ratio of 0.74; 95% Confidence Interval 0.350–1.533). Conclusion: Overall, the likelihood of utilising the Veterans Crisis Line was not related to relationship status. Although the analyses were undertaken with the assumption that calls would be more common in those without access to other sources of social support (such as from a partner) it is possible that outreach efforts have been successful in expanding the appeal of the VCL across different demographic groups. Significance: When safety planning, a clinician may place higher emphasis on the VCL with a patient who has fewer social supports. The present analysis indicates that similar discussion of the VCL may be beneficial for all high-risk patients. Therefore, equal emphasis on the VCL should be included in effective safety planning to prevent injuries, hospitalizations, and deaths.